KOLOM BETON PRACETAK SEBAGAI ALTERNATIF KOLOM ULIN PADA PERUMAHAN DI BANJARMASIN - Nursiah Chairunnisa; Ulfa Fitriati (Universitas Lambung Mangkurat, 2005)
In general housing construction inBanjarmasincan be classified in three type : that is wood construction house, concrete construction and wood construction with brick wall. Special for the a wood construction house have brick wall, generally used column from ulin wood. But from some assessment reason and construction limitation by ulin wood this time, hence in this research try to give scheme alternative with usage precast concrete column at wood construction house have brick wall in BanjarmasinIntention of this research is to study elegibility of ulin column replacement with precast concrete column cover the nature of technical and execution phase making of precast concrete column. Concrete precast column which used in this scheme of designed as according to ulin column dimension to be replaced with by virtue of structural reason, egreement with other element .In research aim to analyze that construction house with competent and valid precast concrete column to be utilized and weared in practice in the place of ulin column. Validasi Elegibility of usage precast concrete column evaluated from some aspect covering assessment about and desain strength of pracetak concrete column at the time of comparison and scheme strength of ulin column with precast concrete column.